Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan iBox Area Bogor dan Depok - Hanan, Muhammad; Siagian, Sabarrudin (CV Warnak Johanna Nusantara, 2026)
This study aims to examine the influence of leadership style and work motivation on employee performance at PT Erajaya Swasembada Tbk (iBox) in the Bogor and Depok areas. The research is driven by the importance of human resource quality, particularly in the electronic retail sector, which heavily relies on employee performance. The study applies a quantitative approach with a causal associative design. The sample consists of 67 respondents, including iBox employees and team leaders. Data were collected through observation, interviews, and questionnaires. The analysis was conducted using multiple linear regression with SPSS version 26. The results indicate that both leadership style and work motivation have a positive and significant influence on employee performance, both individually and simultaneously. These findings emphasize that supportive leadership and high work motivation can enhance performance, providing a foundation for more human-centered and productive managerial strategies